(untitled) (International Journal of Current Engineering and Technology, 2015)
The various design procedures, which are adopted in practical applications to evaluate the seismic response, are usually based on linear elastic structural behavior. However these procedures cannot compute the damage levels of the buildings effectively, for this purpose more accurate methods of analyses, which can predict the real behavior of building under strong seismic actions, are required. The non-linear dynamic analysis is the most rigorous method, but it is too complex and time consuming method for practical application. The non-linear static pushover analysis seems to be a more rational method for estimating the lateral strength and the distribution of inelastic deformations. There has been increasing trend toward the use of pushover analysis as a tool for evaluating the earthquake resistance and safety of structure in the Earthquake Engineering field Since earthquake forces are random in nature & unpredictable, the engineering tools needs to be sharpened for analyzing structures under the action of these forces. Performance based design is gaining a new dimension in the seismic design philosophy wherein the near field ground motion (usually acceleration) is to be considered. Earthquake loads are to be carefully modeled so as to assess the real behavior of structure with a clear understanding that damage is expected but it should be regulated. This study focuses on pushover analysis of multistory RC framed buildings subjecting them to monotonically increasing lateral forces until the preset performance level (target displacement) is reached. A performance-based design is aimed at controlling the structural damage based on precise estimations of proper response parameters.